2020
DOI: 10.1515/rams-2020-0024
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification methods of ceramic filler in ceramic-carbon fibre composites for bioengineering applications – A systematic review

Abstract: The present review paper focuses on the current state of the art of the alumina-silicate ceramics and surface modifications of ceramics dedicated as fillers in composites with carbon fiber. The use of aluminum-silicates in the form of a cenosphere due to their outstanding properties, i.e., low density, high hardness, and total chemical inertness seem to be promising in biomaterial engineering applications. First of all, the possibilities of the composites application in orthopedic and prosthetic implantology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 127 publications
0
13
0
Order By: Relevance
“…The main technological problems of PCCs, regardless of the processing method (injection molding or additive manufacturing), occur from the improper adhesion between the polymer matrix and the ceramic and homogeneous filler dispersions in the matrix [ 25 , 26 ]. Obtaining a homogeneous filler dispersion in the matrix is necessary to obtain a smooth composite surface, flexural and fatigue strength, controlled shrinkage, and crack resistance during polymerization, and to ensure the same physical and chemical properties throughout the material.…”
Section: Introductionmentioning
confidence: 99%
“…The main technological problems of PCCs, regardless of the processing method (injection molding or additive manufacturing), occur from the improper adhesion between the polymer matrix and the ceramic and homogeneous filler dispersions in the matrix [ 25 , 26 ]. Obtaining a homogeneous filler dispersion in the matrix is necessary to obtain a smooth composite surface, flexural and fatigue strength, controlled shrinkage, and crack resistance during polymerization, and to ensure the same physical and chemical properties throughout the material.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the MWCNTs-COOH/PEEK composites, it can be observed that the interface between PEK-C-OH-g-MWCNTs-COOH and the PEEK matrix was blurred and dispersed more homogeneous, and no obvious aggregation phenomenon of PEK-C-OH-g-MWCNTs-COOH was found, indicating that the compatibility of the modified carbon nanotubes with the PEEK matrix was increased. Before grafting, the unmodified carbon nanotubes may agglomerate due to the van der Waals force between the carbon nanotubes and the phase separation effect caused by the low compatibility of the two, while the grafted carbon nanotubes and PEEK The compatibility is improved and the occurrence of agglomeration is reduced [ 30 , 31 , 32 ]. By chemical grafting, the aggregation of MWCNTs-COOH was significantly weakened, so that MWCNTs-COOH can be relatively uniformly dispersed in the PEEK matrix, which facilitates sufficient lapping between the fillers and the formation of a large number of thermally conductive and electron-conductive networks, which is conducive to the transport of phonons and electrons.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, when the value of ΔG°a ds is about − 20kJ•mol − 1 , the steel sheet and the organic molecules interact through electrostatic at this time. When the value of ΔG°ads is around − 40kJ•mol − 1 , the steel sheet and organic molecules are adsorbed by chemical interaction [29][30][31][32]. According to the table, the range of ΔG°ads of nano-SiO 2 @OBQA is between − 28 and − 37kJ•mol − 1 , indicating that the two are mainly through chemical adsorption.…”
Section: Adsorption Isotherm Modelmentioning
confidence: 99%